Relationship between Knowledge Sharing and Innovative Tendencies and Job Performance among High School Principals in Bandar Abbas - Mahnoosh Abedini (Iranian Journal of Educational Research)
Objective: In the present study the relationship between knowledge Sharing and innovative tendencies and job performance   among high school principals in Bandar Abbas. Methods: A descriptive survey was used for the study. For this purpose, 93 high school principals participated in this study. Participants filled explicit knowledge questionnaire, implicit knowledge questionnaire, innovative tendencies questionnaire and job performance questionnaire. Structural equation modeling was used for data analysis using SMART PLS. Results: Findings indicated that innovative tendencies, explicit knowledge and implicit knowledge had a positive significant effect on job performance. Explicit knowledge and implicit knowledge had a positive significant effect on innovative tendencies. In conclusion, findings emphasized the role of knowledge sharing and innovative tendencies on job performance of High School Principals. Conclusions: The results of this study indicated that the relationship between knowledge Sharing and innovative tendencies and job performance among high school principals could provide valuable guidance for increasing motivation and actualizing their potential powers. As an important predicator of knowledge Sharing and innovative tendencies and job performance played a significant role in As an important predictor of knowledge sharing and innovative tendencies, job performance played a significant role in driving organizational success and fostering a culture of continuous improvement within the educational environment.